EXPERIMENTAL RESEARCH TECHNIQUE OF RETAINING WALLS OF A SPECIAL TYPE - Timchenko, R. A.; Krishko, D. A.; Savenko, V. O. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article reviewed the issue of wide use of the retaining walls in construction. It is established the existing retaining walls are not designed for additional forces from horizontal soil displacement that consequently leads to the destruction of the structure. In this regard, there is a need for the development of new structural solutions for retaining walls. The purpose of the research is to develop the technique for conducting experimental studies of the contact interaction of retaining walls and a deformable base. The experiments were carried out on small-scale models in a specially designed tray. At modeling was applied the method of the expanded similarity in which geometrical, mechanical and power analogues with a real object are maintained. As base soil, the models used loamy structure. Models of retaining walls were made on a digital 3D model. A technique for conducting experimental studies of the contact interaction of retaining walls and a deformable base has been developed. The technique is universal and will allow carrying out model experiments under equal conditions, which will ensure reliable results.
Keywords: technique; experiment; model; foundation; retaining wall